Influencia de contaminaciones causadas por microorganismos oportunistas en ratones de la cepa BALB/c.Fox1nu transplantada con la línea tumoral humana A549 - Ayala, Miguel Ángel; Cagliada, María del Pilar; Milocco, Silvana; Carriquiriborde, Martín; Laborde, Juan Martín; Gentil, F.; Resasco, Agustina; Maschi, Fabricio; Principi, Guido; Carbone, Cecilia (Analecta Veterinary, 2013)
Among immunodeficient mouse strains there is the BALB/c.Fox1nu which is used as animal model for transplantation of human tumors. These mice are produced under strict sanitary barriers and should be free of their specific pathogens, among them, the most frequent opportunistic are Pseudomonas aeruginosa, Klebsiella oxytoca, Proteus mirabilis and Citrobacter spp. The aim of this study was to evaluate the interference caused by opportunistic pathogens P. aeruginosa, K. oxytoca, P. mirabilis and Citrobacter spp. BALB/c.Fox1nu hundred female mice of 4 to 6 weeks were divided into ten groups (G) of 10 animals each: G1, transplanted with tumor cell line A549, G2 inoculated with Pseudomonas aeruginosa, G3 inoculated with K. oxytoca; G4 inoculated with P. mirabilis, G5, inoculated with Citrobacter spp, G6 tumor line transplanted and inoculated with P. aeruginosa, G7 transplanted tumor line and inoculated with K. oxytoca, G8 transplanted tumor line and inoculated with P. mirabilis, G9 transplanted tumor line and inoculated with Citrobacter spp. and G10 control. Seven of the 10 animals showed tumor growth in G1, G2 and G 5mice showed no clinical signs, animals from G6 to G9 showed no clinical symptoms and behaved as tumor growth in the 7 mice of G1. It was concluded that these infections are not fatal opportunistic pathogens in mice BALB/c.Fox1nu and do not interfere with tumor development.